IMPROVING STUDENTS' UNDERSTANDING AND MOTIVATION ON ELECTRICAL CIRCUIT TOPIC THROUGH MULTIPLE INTELLIGENCE BASED LEARNING - Siti Kalimaya, - (2020)
The research aims to identify the effect of implementing multiple intelligence based learning to improve students' understanding and motivation on electrical circuit topic. Totally 66 of 8th grade junior high school students were selected through convenience sampling technique as experimental group subjects of this research. The experimental group divided into two categories as higher and lower achiever class based on school privacy. The experimental group was instructed to learn through multiple intelligence based learning as the treatment in learning electrical circuit topic. The treatment given lasted for 6 meetings in 6 weeks and conducted using one group pre-test and post-test design. To see the effect of the treatment on students' understanding, an achievement test about electrical circuit topic which consisted of 24 items was distributed and analyzed using SPSS. The result showed that normalized gain value of the whole participants was 0.28 which categorized as a low improvement. In other word, students' understanding on electrical circuit topic improved after being taught by multiple intelligence based learning. Meanwhile students' motivation was measured by a Likert-scale questionnaire have been developed by other researcher which consisted of six aspects in total 35 items. The overall result showed that there was an improvement in students' motivation after being taught by multiple intelligence based learning.